Green manufacturing—performance of a biodegradable cutting fluid. Issue 13 (3rd October 2017) - Katna, Rahul; Singh, Kanwarjeet; Agrawal, Narayan; Jain, Swati
ABSTRACT: Huge quantity of petroleum and mineral-based cutting fluids mixed with carcinogenic additives to increase their performance is used every year in the manufacturing industry. Application of such fluids poses a serious hazard to the environment, workers, and personnel who directly or indirectly come in contact with them. Disposal of these cutting fluids without neutralization has a high potential of contaminating the water bodies and affects the aquatic life. Various vegetable-based cutting fluids have been formulated from edible oils, but less work is reported on non-edible oils. In this work, non-edible neem oil was used as a base oil and a food grade emulsifier was used. Thus, the cutting fluid is totally biodegradable. Various cutting fluids were formulated, and then, experiments were done on EN8 with uncoated carbides on lathe machine and various results reported. The neem oil has inherent anti-microbial properties and thus prevents microbial contamination for a long period of time. This newly developed cutting fluid does not require any neutralization before disposal.